GAMEMOVE MOTOR SKILL ASSESSMENT MODE AND ITS APPLICATION IN THE ANALYSIS OF MOTOR PERFORMANCE IN AGING INDIVIDUALS - Cavalheiro, Geovani Rafaele Lima; Borges, Sílvia Cardoso; Sidekum, Djuli Margô Naissinger; Berlese, Denise Bolzan; dos Santos, Geraldine Alves (Seven Editora, 2026)
This study analyzed the motor performance of individuals undergoing the aging process, participants of the Gerontology Center at Feevale University, mediated by the active digital game GameMove Motor Skill. The research is characterized as exploratory, quantitative, and cross-sectional. The sample consisted of 102 aging individuals (76 females and 26 males), all participants of the Feevale Gerontology Center. Data were presented using absolute and relative frequencies, measures of central tendency, and dispersion. Normality was tested using the Kolmogorov-Smirnov test, while the Mann-Whitney test compared scores between genders, and the Chi-square test evaluated associations between motor skills and age groups. Analyses were conducted in IBM® SPSS® (v.26.0), adopting a significance level of p ≤ 0.05. The analysis of motor performance in the GameMove Motor Skill revealed no significant differences between sexes in the hitting task, although results showed a favorable trend for men. In the right-leg kicking task, a significant difference was observed in favor of men. This result may be associated with cultural factors that influence oculopedal experiences and the valuation of certain motor skills in the daily lives of aging individuals. The hopping/stationary march test indicated a slight male tendency, but without statistical significance, whereas the balance test revealed significant differences favoring men on both sides, with greater discrepancies observed after the age of 70. The game proved to be a reliable instrument for assessing motor performance in individuals undergoing the aging process, providing support for understanding this performance and for the appropriate prescription of interventions.